Upbringing or Improvement? On the Anti-Christian Roots and Pedagogical Implications of Transhumanism - Markus Lipowicz (Nicolaus Copernicus University in Toruń, 2018)
The main objective of the article is to present the anti-Christian roots of the transhumanist thought and a critical analysis of its pedagogical implications. My main hypothesis is that in the spirit of exclusive humanism the techno-progressive movement pushes forward an anti-Christian image of man, which conceptualizes human existence beyond the foregoing anthropological-pedagogical categories. I will argue that only by reinforcing anthropological reflection upon the meaning of education we might be able to conduct preventive strategies against the contemporary tendencies of the reification and depersonalization of the human. To that end I will try to show that the transhumanist analogy between "enhancement" through education and "technological enhancement" ignores the qualitative difference between two forms of human activity - action and production. In order to stress the anti-Christian character of the concept of technological human enhancement I will try to refer this issue to Joseph Ratzinger's thought on the transition from ancient and scholastic anthropology to the modern image of man as a productive human being, whose existence underlies the logics of constant transformation.